Monetary vs. fiscal policy - Friedman, Milton; Heller, Walter W. (New York: Norton, 1969)
This book is an outcome of a lecture series organized by the Graduate School of Business Administration of New York University in which two renowned Professors, Prof. Milton Friedman and Prof. Walter W. Heller was meant to speak on Monetary Policy and Fiscal Policy respectively as a means to stabilize the economy.
Bibliographical references included in "Notes" (p. [83]-88)
usc 11/04/2018
Loans
Keywords: Monetary policy; Fiscal policy; United States